all you need is in the photo please put only the answer Don't do step by step please answer fast. pleaseeeeeeeeeeplessrs

Quadratic formula is represented by:
[tex]x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}[/tex]Information given:
a=2
b=2
c=-12
Then, we have to substitute each term in the quadratic formula:
[tex]x=\frac{-2\pm\sqrt[]{2^2-4(2)(-12)}}{2(2)}[/tex]Solve for x1:
[tex]\begin{gathered} x_1=\frac{-2+\sqrt[]{4+96}}{4}=\frac{-2+\sqrt[]{100}}{4} \\ x_1=\frac{-2+10}{4}=\frac{8}{4}=2 \end{gathered}[/tex]For x2:
[tex]\begin{gathered} x_1=\frac{-2-\sqrt[]{4+96}}{4}=\frac{-2-\sqrt[]{100}}{4} \\ x_2=\frac{-2-10}{4}=-\frac{12}{4}=3 \end{gathered}[/tex]So, x1=2 and x2=3